Natural color anodized aluminum alloy powder as well as preparation method and application thereof

The natural anodized aluminum alloy powder prepared by remelting aluminum silicon alloy with magnesium silicate, ultrasonic suspension smelting and hypersonic inert gas atomization methods solves the pits and lamination problems of existing aluminum alloy materials after anode corrosion, achieves excellent mechanical properties and natural anodization effect, and is suitable for additive manufacturing of consumer electronic products.

CN120210576APending Publication Date: 2025-06-27JIANGXI BAOHANG ADVANCED MATERIALS CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510217444.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

The existing additively manufactured aluminum alloy materials are prone to pits and printed layers after the anode corrosion, and the mechanical properties do not meet the design requirements, making it difficult to achieve natural anodization.

Method used

Aluminum-magnesium silicon alloy was prepared by remelting aluminum-silicon alloy with magnesium silicate, and a natural anodized aluminum alloy powder was prepared by combining ultrasonic suspension smelting and hypersonic inert gas atomization method to optimize the alloy composition and preparation process to achieve uniform structure and excellent mechanical properties.

Benefits of technology

It has achieved that the aluminum alloy material has no pits or lamination problems after anodization, no color difference, isotropic mechanical properties, tensile strength and elongation meet the design requirements, and is suitable for additive manufacturing of consumer electronic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005287824190000161
    Figure BDA0005287824190000161
  • Figure BDA0005287824190000171
    Figure BDA0005287824190000171
  • Figure BDA0005287824190000173
    Figure BDA0005287824190000173
Patent Text Reader

Abstract

The invention provides natural color anodized aluminum alloy powder and a preparation method and application thereof, and belongs to the field of additive manufacturing. The method comprises the following steps: remelting an aluminum-silicon alloy and magnesium silicate to obtain an aluminum-magnesium-silicon alloy; a mixed raw material is prepared from an aluminum-magnesium-silicon alloy, pure magnesium, pure aluminum and an aluminum-zirconium alloy, and is formed based on ultrasonic suspension smelting and rapid cooling; the aluminum alloy powder comprises the following components in percentage by weight: 1.0-5.0% of Zr, 1.0-5.0% of Al, 1.0-5.0% of Zr, and the balance of aluminum. 0.4 to 1.0 wt% of Mg; 0.4 to 1.0 wt% of Si; the balance is Al and inevitable impurities; wherein the weight ratio of Si to Mg is 1: 1. The material can be used for additive manufacturing molded consumer electronics. According to the method disclosed by the invention, on the premise of reducing the types and the dosage of strengthening elements, the aluminum alloy which is uniform in structure, free of obvious segregation, isotropic in mechanical property, free of the problems of pits and layer lines after anodizing and free of color difference is prepared by adopting an ultrasonic suspension smelting and hypersonic inert gas atomization method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of additive manufacturing materials, and particularly relates to a natural anodized aluminum alloy powder, a preparation method thereof, and an application thereof. Background Art

[0002] Additive manufacturing (also known as 3D printing), as a rapid prototyping process with high degrees of freedom, has a huge promoting effect on the forming of complex structures, the integration of multiple components, and the liberation of design freedom, and is commonly used in fields such as aerospace, medical, automotive, and consumer electronics. In the field of additive manufacturing, titanium alloys have become the most widely used traditional alloy materials due to their excellent mechanical properties. However, the disadvantages of titanium alloys are also obvious, such as difficult processing, poor thermal conductivity, and high cost. Aluminum alloys, with many advantages such as low density, light weight, high specific strength, good thermal conductivity, and low cost, have the potential for rapid popularization in the field of additive manufacturing.

[0003] At present, the aluminum alloys applied to additive manufacturing of consumer electronics are mainly Al-Si-x series alloys, and among them, the 6-series aluminum alloys with magnesium and silicon as the main strengthening elements are the most widely used. However, after the existing Al-Si series alloy materials applicable to the laser additive process are anodically corroded, due to element reactions, problems such as pits and printing layer lines will occur. The main reason for this problem is that the intergranular strengthening phases formed by the strengthening elements disappear under the corrosion of the bath solution, resulting in obvious pits and melt pool boundaries; and due to the high-Si design, the strengthening phases are thick and flaky primary silicon, resulting in the mechanical properties of the alloy, such as tensile strength, yield strength, etc., not meeting the design requirements. In addition, when additive manufacturing is applied to the field of consumer electronics, they usually require high toughness to ensure the safety, reliability, and impact resistance of the structure.

[0004] In order to solve the problem of low strength of aluminum alloys, a large amount of strengthening elements are added to the Al-Si series alloys in the prior art for melting, such as Zr (zirconium), Mn (manganese), Sc (scandium), Gd (gadolinium), Cr (chromium), etc. Although the addition of these elements improves the mechanical properties of the aluminum alloy, the introduction of too many or excessive types of elements will cause defects and serious color deviation problems after anodization of the material, seriously affecting the subsequent coloring treatment; in addition, the introduction of strengthening elements has a poor effect on improving the elongation of the alloy. At present, the room temperature elongation of high-strength aluminum alloys is basically not higher than 15%, and most aluminum alloys are even not higher than 10%.

[0005] Therefore, based on the requirements of the additive manufacturing process, it is necessary to develop special alloys to match it. Starting from the material design end, reselect the material element composition, and develop an additive manufacturing aluminum alloy powder material that can achieve natural anodization, which is specifically used for the additive manufacturing of complex structures of consumer electronics. Summary of the Invention

[0006] In view of this, the object of the present invention is to provide a natural anodized aluminum alloy powder, a preparation method and an application thereof, aiming to solve at least one technical problem in the background art.

[0007] The present invention is implemented as follows:

[0008] The first aspect of the present invention provides a preparation method of a natural anodized aluminum alloy powder, which includes the following steps:

[0009] Remelt the aluminum-silicon alloy and magnesium silicate to obtain an aluminum-magnesium-silicon alloy;

[0010] Make the aluminum-magnesium-silicon alloy, pure magnesium, pure aluminum, and aluminum-zirconium alloy into a mixed raw material, and based on ultrasonic suspension melting and rapid cooling forming, obtain the original powder;

[0011] The original powder is classified and dried to obtain the natural anodized aluminum alloy powder.

[0012] Preferably, the preparation method of the aluminum-magnesium-silicon alloy is: add magnesium silicate powder to the crudely smelted aluminum-silicon alloy melt, and sequentially go through stirring refining and rapid cooling to obtain the aluminum-magnesium-silicon alloy.

[0013] Preferably, the preparation method of the original powder is: sequentially go through ultrasonic vacuum suspension melting, ultrasonic emulsification and co-stationary, and hypersonic inert gas atomization forming to obtain the original powder.

[0014] Preferably, the alloy components in the natural anodized aluminum alloy powder include the following weight percentage compositions:

[0015] Zr 1.0wt% - 5.0wt%;

[0016] Mg 0.4wt% - 1.0wt%;

[0017] Si 0.4wt% - 1.0wt%;

[0018] The balance is Al and unavoidable impurities;

[0019] The weight ratio of Si / Mg in the natural anodized aluminum alloy powder is 1:1;

[0020] The requirements for impurities in the natural anodized aluminum alloy powder are as follows:

[0021] Fe < 0.01wt%; Ni < 0.01wt%; Mo < 0.01wt%; Zn < 0.01wt%; Pb < 0.01wt%;

[0022] Sn < 0.01 wt%; Ti < 0.01 wt%; Mn < 0.01 wt%; C < 0.01 wt%; H < 0.01 wt%; Na < 0.01 wt%; Cu < 0.01 wt%.

[0023] Preferably, the preparation method of the aluminum-magnesium-silicon alloy is specifically operated as follows:

[0024] Weigh the aluminum-silicon alloy and place it in an induction melting furnace. Under the protection of inert gas, carry out rough melting to obtain an aluminum-silicon alloy melt. The temperature range of the rough melting is 650°C to 750°C;

[0025] Add magnesium silicate powder in a preset proportion to the aluminum-silicon alloy melt, and keep it warm and melt for 1h to 4h under the protection of inert gas and mechanical stirring;

[0026] Rapidly cool and form to obtain the aluminum-magnesium-silicon alloy;

[0027] Among them, the dosage of magnesium silicate is 2.0 wt% to 6.0 wt% of the aluminum-silicon alloy.

[0028] Preferably, the preparation method of the original powder is specifically operated as follows:

[0029] Weigh the required amounts of aluminum-magnesium-silicon alloy, pure magnesium, pure aluminum, and aluminum-zirconium alloy, mix them and place them in a suspension melting device. Evacuate to a vacuum degree ≤ 3 Pa, and after reaching the standard, fill with inert gas to standard atmospheric pressure;

[0030] Use ultrasonic suspension to suspend and lift the mixed raw materials, and then heat to 650°C to 750°C to melt into a molten liquid;

[0031] Keep warm and stand still and carry out ultrasonic emulsification for 5 min to 30 min to obtain an alloy liquid;

[0032] Based on the high-speed collision of the inert gas ejected at high speed and the alloy liquid droplets flowing out of the liquid guide tube to achieve atomization. After the alloy liquid is broken into small droplets, it can be cooled to obtain the natural anodized aluminum alloy powder;

[0033] Among them, during the ultrasonic suspension process, the ultrasonic current is set to 15 A to 30 A, and ultrasonic current and power monitoring are set to automatically adjust the ultrasonic current output to prevent ultrasonic attenuation.

[0034] Preferably, the specific operation of the inert gas ejected at high speed is as follows: Fill the atomization disc body below the suspension melting device with inert gas, accelerate through the annular cavity, and eject at high speed from the bottom annular slit. The ejection speed is 4 - 5 Mach, and the annular slit gas outlet angle of the atomization disc body is 52°.

[0035] The second aspect of the present invention provides a natural anodized aluminum alloy powder prepared by the above preparation method.

[0036] The third aspect of the present invention provides an application of a natural anodized aluminum alloy powder prepared by the above preparation method, and the natural anodized aluminum alloy powder is used for additive manufacturing of consumer electronic products;

[0037] The specific method of additive manufacturing is as follows: the natural anodized aluminum alloy powder is subjected to red-light fiber laser SLM printing, annealing, wire cutting, surface treatment, and heat treatment to form, and then air-cooled to obtain an additive manufacturing product.

[0038] Preferably, in the red-light fiber laser SLM printing, the laser power is 350W - 450W, the scanning speed is 1000mm / s - 1400mm / s, and the scanning spacing is 0.08mm - 0.12mm;

[0039] The heat treatment adopts vacuum heat treatment, the holding temperature is 300°C - 500°C, and the holding time is 4h - 6h.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] 1. Under the premise of reducing the types and amounts of strengthening elements, the method of the present invention uses ultrasonic suspension melting + hypersonic inert gas atomization to obtain an aluminum alloy material with uniform structure, no obvious segregation, isotropic mechanical properties after additive manufacturing, no pits, layer pattern problems, and no color difference after anodization, and can be widely promoted in the application field of additive manufacturing of consumer electronic products.

[0042] 2. The present invention melts the raw materials by ultrasonic suspension melting technology. The ultrasonic oscillation generates a suspension force, enabling the metal materials to be melted without contacting other objects. Its advantages include no crucible pollution, uniform electromagnetic stirring, high melting temperature, and being suitable for melting active metals.

[0043] 3. The present invention uses magnesium silicate as a functional agent to modify the main raw material aluminum-silicon alloy of the alloy, refine the grain structure, and strengthen the mechanical properties.

[0044] 4. During the material forming process of the present invention, rapid cooling is carried out by hypersonic inert gas atomization, which can promote the alloy to break through the solid solution limit of the material, and the printed sample of the material presents a hierarchical non-uniform microstructure with fine grain distribution.

[0045] 5. After the anodization treatment of the aluminum alloy material prepared by the present invention, due to the structure of the precipitation strengthening phase, no corrosion pits occur. Due to the hindrance of the precipitation phase, the unit cells do not grow significantly, and the printing layer pattern phenomenon is effectively solved. Specific Embodiments

[0046] In order to make the objectives, technical solutions and advantages of the present invention more clear and understandable, the present invention will be further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0047] A natural anodized aluminum alloy powder, the alloy composition of which comprises the following components by weight percentage: Zr 1.0 wt% to 5.0 wt%; Mg 0.4 wt% to 1.0 wt%; Si 0.4 wt% to 1.0 wt%; the balance is Al and unavoidable impurities; wherein the weight ratio of Si / Mg is 1:1;

[0048] The requirements for impurities in the natural anodized aluminum alloy powder are as follows:

[0049] Fe < 0.01 wt%; Ni < 0.01 wt%; Mo < 0.01 wt%; Zn < 0.01 wt%; Pb < 0.01 wt%;

[0050] Sn < 0.01 wt%; Ti < 0.01 wt%; Mn < 0.01 wt%; C < 0.01 wt%; H < 0.01 wt%; Na < 0.01 wt%; Cu < 0.01 wt%.

[0051] A method for preparing a natural anodized aluminum alloy powder, which comprises steps S1 to S3.

[0052] S1. Remelt an aluminum-silicon alloy and magnesium silicate to obtain an aluminum-magnesium-silicon alloy; specifically including:

[0053] (1-1) Weigh an aluminum-silicon alloy and place it in an induction melting furnace, and carry out rough melting under the protection of an inert gas to obtain an aluminum-silicon alloy melt, and the rough melting range is 650°C to 750°C;

[0054] (1-2) Add a preset proportion of magnesium silicate powder (with a particle size less than 10 μm, preferably a nano-scale magnesium silicate powder with a particle size less than 1 μm) to the aluminum-silicon alloy melt, and keep it warm and melt for 1 h to 4 h under the protection of an inert gas and mechanical stirring. Among them, the dosage of magnesium silicate is 2.0 wt% to 6.0 wt% of the aluminum-silicon alloy;

[0055] (1-3) Rapidly cool and form the alloy melt prepared in step (1-2) to obtain a block-shaped or rod-shaped aluminum-magnesium-silicon alloy.

[0056] In this step, a functional agent magnesium silicate is added to the aluminum-silicon alloy for remelting modification. Its main functions include: (1) strengthening mechanical properties. First, magnesium silicate can be used as an additive to improve the strength and hardness of the aluminum-silicon alloy, enhance its fluidity and thermal stability, and strengthen its corrosion resistance. Second, during the remelting process of the aluminum-silicon alloy, a strengthening phase Mg2Si is formed. Magnesium silicate can promote the precipitation of a small amount of dispersed Mg-Al phases, such as β-Mg 17 Al 12 , in the molten aluminum-silicon alloy, thereby promoting the optimization of yield strength, tensile strength, and elongation; (2) refining the grain structure. First, during the remelting and cooling processes, magnesium silicate can preferentially nucleate heterogeneously in the melt, thus refining primary silicon and eutectic silicon. At the same time, the aluminum-silicon alloy can capture oxygen from magnesium silicate to form fine Al2O3 strengthening phases that are uniformly distributed in a dispersed manner. Alumina can also act as a nucleating agent to further promote grain refinement. The fine grain structure helps to improve the mechanical properties and fatigue resistance of the alloy;

[0057] In specific implementation, the dosage of the functional agent magnesium silicate should not be too small, otherwise its optimization effect on the aluminum-silicon alloy is not significant; nor should the dosage be too large, otherwise it will increase the oxide content in the alloy and affect the mechanical properties of the alloy.

[0058] S2: Aluminum-magnesium-silicon alloy, pure magnesium, pure aluminum, and aluminum-zirconium alloy are made into a mixed raw material, and based on suspension melting and rapid cooling forming, the original powder is obtained;

[0059] Before this step, it is necessary to detect the components in the aluminum-magnesium-silicon alloy obtained in S1, measure the contents of aluminum, magnesium, and silicon, and then weigh other raw materials according to the ingredient requirements to make up the contents of magnesium, aluminum, and zirconium. The specific operations of S2 include:

[0060] (2-1) Weigh the required amounts of aluminum-magnesium-silicon alloy, pure magnesium, pure aluminum, and aluminum-zirconium alloy, mix them and place them in a suspension melting device, evacuate to a vacuum degree ≤ 3 Pa, and after reaching the standard, fill with an inert gas to standard atmospheric pressure;

[0061] (2-2) Use ultrasonic suspension to lift and support the mixed raw materials, and then heat them to 650 °C - 750 °C to melt them into a molten liquid. During the ultrasonic suspension process, the ultrasonic current is set to 15 A - 30 A, and ultrasonic current and power monitoring are set to automatically adjust the ultrasonic current output to prevent ultrasonic attenuation;

[0062] (2-3) Keep warm and stand still and perform ultrasonic emulsification for 5 min - 30 min to obtain an alloy liquid;

[0063] (2 - 4) An inert gas is filled into the atomization disk body below the suspension melting device, accelerated through the annular cavity, and ejected at a high speed from the bottom annular slit. The ejection speed is 4 Mach to 5 Mach, and the gas outlet angle of the annular slit of the atomization disk body is 52°. The inert gas ejected at a high speed collides with the alloy droplets flowing out of the liquid guide tube at a high speed to achieve atomization. After the alloy is broken into small droplets, it can be cooled to obtain the original powder.

[0064] In this step, ultrasonic suspension melting is used to provide a containerless environment for the material, greatly reducing the heat loss caused by the contact between the melt and the melting device, effectively preventing the formation of heterogeneous crystal nuclei, further refining the silicon crystals, improving the material properties, and facilitating the melt to obtain deep undercooling and achieve rapid solidification. By using ultrasonic suspension melting, the phenomenon of insufficient melting of materials at the bottom of the melting process device can be effectively avoided, so that all raw materials are fully melted, and the uniformity and accuracy of the composition are guaranteed.

[0065] Compared with conventional magnetic field suspension, the present invention uses ultrasonic waves as the radiation source for suspension. Under the action of the acoustic standing wave field, the suspended alloy melt can form rich dynamic behaviors such as oscillation, rotation, surface waves, deformation, and atomization. In addition, the ultrasonic waves act on the alloy melt metal to generate a periodic alternating sound field, forming the acoustic streaming effect and the cavitation effect, which can significantly improve the microstructure of the alloy after solidification and refine the grains.

[0066] The rapid cooling (hypersonic inert gas atomization) during the material forming process of the present invention can promote the alloy to break through the solid solubility limit of the material. The printed sample of the material presents a hierarchical non-uniform microstructure with fine grain distribution. On the basis of S1, the primary strengthening phases are nano-particle-like Mg2Si phases and fine Al2O3 strengthening phases dispersed in the matrix, as well as a large number of short rod-like Al3Zr phases distributed at the edges of the unit cells, and β-Mg distributed in an irregular blocky and discontinuous network at the grain boundaries. 17 Al 12 , which comprehensively plays a composite strengthening role on the matrix, hinders the excessive growth of the unit cells, and enables the material to have very excellent strength and toughness matching. After heat treatment, the grain size of the alloy does not change significantly, and there are a considerable number of precipitation phases, further improving the mechanical properties of the material.

[0067] S3. The original powder is classified and dried to obtain the natural anodized aluminum alloy powder.

[0068] The natural anodized aluminum alloy powder prepared by the present invention can be used for additive manufacturing of consumer electronic products. The natural anodized aluminum alloy powder is subjected to red-light fiber laser SLM printing, annealing, wire cutting, surface treatment, and heat treatment to form a shape, and then air-cooled to obtain an additive manufacturing product.

[0069] During the red-light fiber laser SLM printing process, the laser power is 350W - 450W, the scanning speed is 1000mm / s - 1400mm / s, and the scanning spacing is 0.08mm - 0.12mm;

[0070] The heat treatment is carried out by vacuum heat treatment, with the holding temperature being 300°C - 500°C and the holding time being 4h - 6h.

[0071] Example 1

[0072] In this example, an ultrasonic suspension melting + hypersonic inert gas atomization method is used to prepare a natural anodized aluminum alloy powder. Among them: the alloy composition of the aluminum alloy powder, in terms of mass percentage, includes Zr: 1.5wt%; Mg: 1.0wt%; Si: 1.0wt%; for the requirements of impurities in the material, Fe < 0.01; Ni < 0.01; Mo < 0.01; Zn < 0.01; Pb < 0.01; Sn < 0.01; Ti < 0.01; Mn < 0.01; C < 0.01; H < 0.01; Na < 0.01; Cu < 0.01; the balance is Al, where the ratio of Si / Mg is 1:1.

[0073] The preparation method includes the following steps:

[0074] S1. Weigh the aluminum-silicon alloy and 4.0wt% of magnesium silicate powder (particle size = 0.5μm - 1μm) of the aluminum-silicon alloy. First, place the aluminum-silicon alloy in an induction melting furnace and heat it to 750°C under the protection of inert gas for rough melting to obtain an aluminum-silicon alloy melt; then add the magnesium silicate powder and keep it melting for 2h under the protection of inert gas and mechanical stirring; after degassing and slag removal, pour the molten alloy liquid into a pre-prepared water-cooled crystallizer, and achieve rapid cooling through the rapid heat conduction of the crystallizer to obtain an aluminum-magnesium-silicon alloy.

[0075] S2. Weigh the required amount of aluminum-magnesium-silicon alloy, pure magnesium, pure aluminum, and aluminum-zirconium alloy, mix them and place them in a suspension melting device, evacuate to a vacuum degree ≤ 3Pa, and after reaching the standard, fill it with inert gas to standard atmospheric pressure; set the ultrasonic current to 20A to suspend and lift the raw materials. To prevent ultrasonic attenuation, conduct automatic monitoring of current and power and automatically adjust the current output; heat the materials in suspension to 750°C to melt them into an alloy liquid, then keep it standing for 10min, fully stand, and make it uniformly diffused through ultrasonic emulsification to obtain an alloy melt; fill inert gas in the atomization disc body below the melting device, accelerate through the annular cavity, and shoot out at high speed from the bottom annular gap with a shooting speed of 4 Mach. Drop the prepared alloy liquid below the liquid guide pipe for high-speed collision for atomization. The air outlet angle of the annular gap of the atomization disc body is 52°, and after it is broken into small droplets, it can be cooled to obtain the original powder.

[0076] S3. The original powder is classified and dried to obtain the aluminum alloy powder.

[0077] The aluminum alloy powder prepared in the embodiment of the present invention is used in the printing process of additive manufacturing and forming. The printing specifically refers to red-light fiber laser SLM printing, with a laser power of 370 W, a scanning speed of 1400 mm / s, a scanning spacing of 0.11 mm. After annealing, wire cutting, surface treatment, and vacuum heat treatment at 400 °C for 4 h, and then air cooling to form, the printed product can be obtained. The performance of the product material is tested, and the results are shown in Table 1 and Table 2.

[0078] Example 2

[0079] In this embodiment, an ultrasonic suspension melting + hypersonic inert gas atomization method is used to prepare a natural anodized aluminum alloy powder. Among them, the alloy composition of the aluminum alloy powder, in terms of mass percentage, includes Zr: 2.5 wt%; Mg: 0.8 wt%; Si: 0.8 wt%. The requirements for impurity elements in the material are Fe < 0.01; Ni < 0.01; Mo < 0.01; Zn < 0.01; Pb < 0.01; Sn < 0.01; Ti < 0.01; Mn < 0.01; C < 0.01; H < 0.01; Na < 0.01; Cu < 0.01, and the balance is Al. Among them, the ratio of Si / Mg is 1:1.

[0080] The preparation method includes the following steps:

[0081] S1. Weigh the aluminum-silicon alloy and 4.0 wt% of magnesium silicate of the aluminum-silicon alloy. First, place the aluminum-silicon alloy in an induction melting furnace and heat it to 720 °C for rough melting under the protection of an inert gas to obtain an aluminum-silicon alloy melt. Then add magnesium silicate powder and keep it warm and melt for 2.5 h under the protection of an inert gas and mechanical stirring. After degassing and slag removal, pour the molten alloy liquid into a pre-prepared water-cooled crystallizer, and achieve rapid cooling through the rapid heat conduction of the crystallizer to obtain an aluminum-magnesium-silicon alloy.

[0082] S2. Weigh the required amount of aluminum-magnesium-silicon alloy, pure magnesium, pure aluminum, and aluminum-zirconium alloy, mix them and place them in a suspension melting device, evacuate to a vacuum degree ≤ 3 Pa, and after reaching the standard, fill it with an inert gas to standard atmospheric pressure. Set the ultrasonic current to 20 A to suspend and lift the raw materials. To prevent ultrasonic attenuation, perform automatic monitoring of current and power and automatically adjust the current output. After heating the materials in suspension to 720 °C and melting them into an alloy liquid, keep it warm and stand for 15 min, fully stand, and make it uniformly diffused through ultrasonic emulsification to obtain an alloy melt. Fill an inert gas in the atomization disc body below the melting device, accelerate through the annular cavity, and eject it at a high speed from the bottom annular gap, with a shooting speed of 4 Mach. Drop the prepared alloy liquid below the liquid guide tube for high-speed collision for atomization. The air outlet angle of the annular gap of the atomization disc body is 52°. After breaking it into small droplets, cool it to obtain the original powder.

[0083] S3. The raw powder is classified and dried to obtain aluminum alloy powder.

[0084] The aluminum alloy powder prepared in this example is used in the printing process of additive manufacturing. The printing specifically refers to red-light fiber laser SLM printing, with a laser power of 400 W, a scanning speed of 1200 mm / s, a scanning spacing of 0.12 mm. After annealing, wire cutting, surface treatment, and vacuum heat treatment at 450 °C for 4 h, followed by air cooling to form, the printed product can be obtained. The performance of the product material is tested, and the results are shown in Table 1 and Table 2.

[0085] Example 3

[0086] In this example, an ultrasonic suspension melting + hypersonic inert gas atomization method is used to prepare a natural anodized aluminum alloy powder. Among them: the alloy composition of the alloy powder, by mass percentage, includes Zr: 4.5 wt%; Mg: 0.9 wt%; Si: 0.9 wt%; for the requirements of impurities in the material, Fe < 0.01; Ni < 0.01; Mo < 0.01; Zn < 0.01; Pb < 0.01; Sn < 0.01; Ti < 0.01; Mn < 0.01; C < 0.01; H < 0.01; Na < 0.01; Cu < 0.01; the balance is Al, where the ratio of Si / Mg is 1:1.

[0087] The preparation method includes the following steps:

[0088] S1. Weigh the aluminum-silicon alloy and 4.0 wt% of magnesium silicate of the aluminum-silicon alloy. First, place the aluminum-silicon alloy in an induction melting furnace and heat it to 700 °C for rough melting under inert gas protection to obtain an aluminum-silicon alloy melt; then add magnesium silicate powder and keep it melting for 4 h under inert gas protection and mechanical stirring; after degassing and slag removal, pour the molten alloy liquid into a pre-prepared water-cooled crystallizer, and achieve rapid cooling through the rapid heat conduction of the crystallizer to obtain an aluminum-magnesium-silicon alloy.

[0089] S2. Weigh the required amount of aluminum-magnesium-silicon alloy, pure magnesium, pure aluminum, and aluminum-zirconium alloy, mix them and place them in a suspension melting device, evacuate to a vacuum degree ≤ 3 Pa, and after reaching the standard, fill it with inert gas to standard atmospheric pressure; set the ultrasonic current to 20 A to suspend and lift the raw materials. To prevent ultrasonic attenuation, monitor the current and power automatically, adjust the current output automatically, heat the materials in suspension to 700 °C to melt them into an alloy liquid, keep it standing for 20 min, fully stand, and make it uniform through ultrasonic emulsification; fill inert gas in the atomization disk body below the melting device, accelerate through the annular cavity, and shoot out at high speed from the bottom annular slit, with a shooting speed of 5 Mach. Drop the prepared alloy liquid below the liquid guide tube for high-speed collision for atomization. The outlet angle of the annular slit of the atomization disk body is 52°. After breaking it into small droplets, cool it to obtain the raw powder.

[0090] S3. The original powder is classified and dried to obtain aluminum alloy powder.

[0091] The aluminum alloy powder obtained in this embodiment is used in the printing process of additive manufacturing. The printing specifically refers to red light fiber laser SLM printing, the laser power is 390W; the scanning speed is 1000mm / s; the scanning spacing is 0.08mm; and then annealing, wire cutting, surface treatment, 300℃ vacuum heat treatment for 6h, and then air cooling molding to obtain the printed product. The performance of the product material is tested, and the results are shown in Tables 1 and 2.

[0092] Example 4

[0093] On the basis of Example 3, the amount of magnesium silicate was adjusted to 2 wt %, and other reaction conditions and parameters were consistent with those in Example 3.

[0094] The properties of the additive manufacturing printing product material obtained in this embodiment were tested, and the results are shown in Tables 1 and 2.

[0095] Example 5

[0096] On the basis of Example 3, the amount of magnesium silicate was adjusted to 6 wt %, and other reaction conditions and parameters were consistent with those in Example 3.

[0097] The properties of the additive manufacturing printing product material obtained in this embodiment were tested, and the results are shown in Tables 1 and 2.

[0098] Example 6

[0099] On the basis of Example 3, the ultrasonic current was adjusted to 15 A, and other reaction conditions and parameters were consistent with those in Example 3.

[0100] The properties of the additive manufacturing printing product material obtained in this embodiment were tested, and the results are shown in Tables 1 and 2.

[0101] Example 7

[0102] On the basis of Example 3, the ultrasonic current was adjusted to 25 A, and other reaction conditions and parameters were consistent with those in Example 3.

[0103] The properties of the additive manufacturing printing product material obtained in this embodiment were tested, and the results are shown in Tables 1 and 2.

[0104] Example 8

[0105] On the basis of Example 3, the ultrasonic current was adjusted to 30 A, and other reaction conditions and parameters were consistent with those in Example 3.

[0106] The properties of the additive manufacturing printing product material obtained in this embodiment were tested, and the results are shown in Tables 1 and 2.

[0107] Comparative Example 1

[0108] Based on Example 3, the electromagnetic levitation melting in S2 was adjusted, and electromagnetic field levitation melting without ultrasonic action was adopted. Other reaction conditions and parameters were the same as those in Example 3.

[0109] Specifically, in this comparative example, S2 was as follows: Weigh the required amounts of aluminum-magnesium-silicon alloy, pure magnesium, pure aluminum, and aluminum-zirconium alloy, mix them and place them in a levitation melting device. Evacuate to a vacuum degree of ≤3 Pa, and after reaching the standard, fill with inert gas to standard atmospheric pressure. Set the electromagnetic field frequency to 30 kHz to levitate and hold the raw materials. Heat the materials in suspension to 700 °C to melt them into alloy liquid, then keep it warm and static for 20 min. After sufficient static settling and uniform diffusion, an alloy melt is obtained. Fill inert gas into the atomization disc body below the melting device, accelerate through the annular cavity, and eject it at high speed from the bottom annular slit with a shooting speed of 5 Mach. Drop the obtained alloy liquid below the liquid guide tube for high-speed collision atomization. The air outlet angle of the annular slit of the atomization disc body is 52°. After breaking it into small droplets, cool it to obtain the original powder.

[0110] Test the properties of the material of the additive manufacturing formed and printed product prepared in this comparative example. The results are shown in Table 1 and Table 2.

[0111] Comparative Example 2

[0112] In this comparative example, based on Example 3, the levitation melting in S2 was adjusted to conventional melting, and other reaction conditions and parameters were the same as those in Example 3.

[0113] Specifically, in this Comparative Example 2, S2 was as follows: Weigh the required amounts of aluminum-magnesium-silicon alloy, pure magnesium, pure aluminum, and aluminum-zirconium alloy, mix them and place them in a vacuum melting device. Evacuate to a vacuum degree of ≤3 Pa, and after reaching the standard, fill with inert gas to standard atmospheric pressure. Heat it to 700 °C to melt it into alloy liquid, then keep it warm and static for 20 min. After sufficient static settling and uniform diffusion, an alloy melt is obtained. Fill inert gas into the atomization disc body below the melting device, accelerate through the annular cavity, and eject it at high speed from the bottom annular slit with a shooting speed of 5 Mach. Drop the obtained alloy liquid below the liquid guide tube for high-speed collision atomization. The air outlet angle of the annular slit of the atomization disc body is 52°. After breaking it into small droplets, cool it to obtain the original powder.

[0114] Test the properties of the material of the additive manufacturing formed and printed product prepared in this comparative example. The results are shown in Table 1 and Table 2.

[0115] Comparative Example 3

[0116] On the basis of Example 3, this comparative example deletes step S1, directly weighs the aluminum-magnesium-silicon alloy, pure magnesium, pure aluminum, and aluminum-zirconium alloy according to the component requirements, and performs ultrasonic suspension melting + hypersonic inert gas atomization method; other reaction conditions and parameters are the same as those in Example 3.

[0117] The properties of the additive manufacturing forming and printing product materials prepared in this comparative example were tested, and the results are shown in Tables 1 and 2.

[0118] Comparative Example 4

[0119] On the basis of Example 3, this comparative example adjusts the dosage of magnesium silicate to 1 wt%; other reaction conditions and parameters are the same as those in Example 3.

[0120] The properties of the additive manufacturing forming and printing product materials prepared in this comparative example were tested, and the results are shown in Tables 1 and 2.

[0121] Comparative Example 5

[0122] On the basis of Example 3, this comparative example adjusts the dosage of magnesium silicate to 7 wt%; other reaction conditions and parameters are the same as those in Example 3.

[0123] The properties of the additive manufacturing forming and printing product materials prepared in this comparative example were tested, and the results are shown in Tables 1 and 2.

[0124] Comparative Example 6

[0125] On the basis of Example 3, in this comparative example, the functional agent in step S1 is added to S2, and step S1 is deleted; other reaction conditions and parameters are the same as those in Example 3.

[0126] The melting steps of this comparative example are as follows: Weigh the required amounts of aluminum-silicon alloy, pure magnesium, pure aluminum, aluminum-zirconium alloy, and magnesium silicate, mix them and place them in a suspension melting device, evacuate to a vacuum degree of ≤3 Pa, and after reaching the standard, fill it with inert gas to standard atmospheric pressure; Set the ultrasonic current to 20 A to suspend and lift the raw materials. To prevent ultrasonic attenuation, automatic monitoring of current and power is carried out, and the current output is automatically adjusted. The materials in suspension are heated to 700 °C to melt into alloy liquid, then kept warm and static for 20 min, fully static, and uniformly diffused through ultrasonic emulsification to obtain alloy melt; Fill inert gas in the atomization disk body below the melting device, accelerate through the annular cavity, and shoot out at high speed from the bottom annular gap, with a shooting speed of 5 Mach. The obtained alloy liquid is dropped below the liquid guide pipe for high-speed collision for atomization. The outlet angle of the annular gap of the atomization disk body is 52°. After it is broken into small droplets, it can be cooled to obtain the original powder.

[0127] The properties of the additive manufacturing forming and printing product materials prepared in this comparative example were tested, and the results are shown in Tables 1 and 2.

[0128] Comparative Example 7

[0129] On the basis of Example 3, Zr in the alloy composition was adjusted to 5.2 wt%; other reaction conditions and parameters were the same as those in Example 3.

[0130] The properties of the additive manufacturing formed and printed product materials prepared in this comparative example were tested, and the results are shown in Tables 1 and 2.

[0131] Comparative Example 8

[0132] On the basis of Example 3, Zr in the alloy composition was adjusted to 0.8 wt%; other reaction conditions and parameters were the same as those in Example 3.

[0133] The properties of the additive manufacturing formed and printed product materials prepared in this comparative example were tested, and the results are shown in Tables 1 and 2.

[0134] Comparative Example 9

[0135] On the basis of Example 3, Mg in the alloy composition was adjusted to 0.3 wt% and Si was adjusted to 0.3 wt%; the adjustment of Mg and Si in the alloy composition in this comparative example was made according to the raw material dosage in step S2, and other reaction conditions and parameters were the same as those in Example 3.

[0136] The properties of the additive manufacturing formed and printed product materials prepared in this comparative example were tested, and the results are shown in Tables 1 and 2.

[0137] Comparative Example 10

[0138] On the basis of Example 3, Mg in the alloy composition was adjusted to 1.1 wt% and Si was adjusted to 1.1 wt%; the adjustment of Mg and Si in the alloy composition in this comparative example was made according to the raw material dosage in step S2, and other reaction conditions and parameters were the same as those in Example 3.

[0139] The properties of the additive manufacturing formed and printed product materials prepared in this comparative example were tested, and the results are shown in Tables 1 and 2.

[0140] Mechanical property tests and chromaticity detection were carried out on the additive manufacturing products prepared in Examples 1 to 8 and Comparative Examples 1 to 10.

[0141] Among them, the mechanical property test method referred to the method in GB / T 39254-2020 "General Rules for Evaluating the Mechanical Properties of Additive Manufactured Metal Parts", and the results are shown in Table 1.

[0142] Table 1

[0143]

[0144]

[0145] The additively manufactured products prepared in Examples 1 to 8 and Comparative Examples 1 to 10 were anodized. Specifically, the additively manufactured products prepared in each example and comparative example were used as anodes and placed in a sulfuric acid-based electrolyte for electrification treatment. An alumina film was formed on the product surface by electrolysis, and then a color difference meter was used to detect the brightness and surface color difference. Among them, L represents the brightness of the product, and 0 - 100 indicates from black to white; a represents the red-green color of the product, + indicates red, and - indicates green; b represents the yellow-blue color of the product, + indicates yellow, and - indicates blue. Take the L, a, and b values at more than 10 consecutive test points of the product and calculate the color difference value. In the formula, △L, △a, and △b respectively represent the differences between the standard color and the test color in terms of brightness, red-green color, and yellow-blue color; △E < 0.25 indicates that the color difference is very small or non-existent, △E of 0.25 - 0.5 indicates that the color difference is tiny, △E of 0.5 - 1.0 indicates that the color difference is medium and the gap is relatively obvious; △E > 1.0 indicates that the color difference is large and the gap is very obvious, and it is only acceptable in specific applications. The test results are shown in Table 2.

[0146] Table 2

[0147]

[0148]

[0149] Referring to the data of Examples 1 to 8 in Table 1 and Table 2, it can be seen that the aluminum alloy material prepared by the ultrasonic suspension melting + hypersonic inert gas atomization method of the present invention has a tensile strength and lower yield strength of more than 400 MPa, and the elongation rate is all above 15%; the brightness L value is all greater than 85, the a value and b value are both between ±0.5, and △E is all less than 0.5, belonging to the unbiased color range and colorless difference range, meeting the requirements of aluminum alloys for natural color anodization, and can be widely used in consumer electronic products.

[0150] In Comparative Examples 1 and 2, the suspension without ultrasound and the conventional melting method were respectively used. Compared with Example 3, the tensile strength, lower yield strength, and elongation rate of the products prepared in Comparative Examples 1 and 2 decreased significantly, and the brightness L value was all less than 85, the a value and b value were both outside ±0.5, and △E was all greater than 0.5, belonging to the obvious color deviation range and medium color difference range.

[0151] In Comparative Example 3, the aluminum-silicon alloy was remelted with the functional agent magnesium silicate missing, and the tensile strength, lower yield strength, and elongation rate of the prepared product were all lower than those of Example 3, and there were color deviation and color difference.

[0152] From the comparison between Example 3 to Example 5, Comparative Example 4 and Comparative Example 5, it can be seen that as the dosage of magnesium silicate increases, both the tensile strength and the lower yield strength increase, but the elongation shows a trend of increasing first and then decreasing; when the dosage of magnesium silicate is less than 2wt% of the aluminum-silicon alloy, the tensile strength and the lower yield strength are lower than 400MPa; after the dosage of magnesium silicate exceeds 6wt% of the aluminum-silicon alloy, the elongation drops below 15%. In view of this, the dosage of magnesium silicate exceeds 2wt% - 6wt% of the aluminum-silicon alloy.

[0153] In Comparative Example 6, the functional agent magnesium silicate was melted synchronously with the alloy raw materials. The tensile strength, lower yield strength and elongation of the obtained product were all lower than those of Example 3, and there were color deviation and color difference, but the mechanical properties, color deviation and color difference were better than those of Comparative Example 3 without the functional agent magnesium silicate. The reason is that when the free magnesium silicate is melted synchronously with the alloy raw materials (pure magnesium, pure aluminum, etc.), an excessive amount of β-Mg 17 Al 12 will precipitate, forming large-sized grains, and the free magnesium silicate will form slag with trace impurities in the raw materials, which is not conducive to subsequent atomization and cooling forming.

[0154] From the comparison between Example 3, Example 6 to Example 8, as the ultrasonic current increases, the mechanical properties, color deviation and color difference are all optimized to a certain extent. The reason is that as the ultrasonic current increases, it is beneficial to the suspension melting effect.

[0155] From the comparison between Example 3, Comparative Example 7 to Comparative Example 10, it can be seen that as the components of Zr, Mg, and Si are adjusted, the mechanical properties and / or color deviation and color difference change. For example, when Zr is excessive, the tensile strength, lower yield strength and elongation are all relatively high, but the values of L, a, b, and △E do not meet the requirements. If Zr is too little, the above performance is opposite; when Mg and Si are excessive, the tensile strength and lower yield strength increase but the elongation decreases, and the values of L, a, b, and △E do not meet the requirements; if Mg and Si are too little, the above performance is opposite.

[0156] The above-described embodiments only represent several implementation manners of the present invention. The description is relatively specific and detailed, but it should not be construed as a limitation on the scope of the present invention patent. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present invention, several deformations and improvements can still be made, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent should be subject to the appended claims.

Claims

1. A method for preparing a natural anodized aluminum alloy powder, characterized in that: The preparation method comprises the following steps: Aluminum-magnesium-silicon alloy is obtained by remelting aluminum-silicon alloy and magnesium silicate; Aluminum-magnesium-silicon alloy, pure magnesium, pure aluminum, and aluminum-zirconium alloy are made into mixed raw materials, and raw powder is obtained based on ultrasonic suspension melting and rapid cooling molding; The original powder is classified and dried to obtain the natural color anodized aluminum alloy powder.

2. The method for preparing a natural anodized aluminum alloy powder according to claim 1, characterized in that: The preparation method of the aluminum-magnesium-silicon alloy is as follows: magnesium silicate powder is added to a roughly refined aluminum-silicon alloy melt, and the aluminum-magnesium-silicon alloy is obtained by stirring, refining, and rapidly cooling in sequence.

3. The method for preparing a natural anodized aluminum alloy powder according to claim 1, characterized in that: The preparation method of the original powder is: the original powder is obtained by sequentially performing ultrasonic vacuum suspension melting, ultrasonic emulsification coordinated standing, and hypersonic inert gas atomization molding.

4. The method for preparing a natural anodized aluminum alloy powder according to any one of claims 1 to 3, characterized in that: The alloy components in the natural anodized aluminum alloy powder include the following weight percentage compositions: Zr 1.0wt%~5.0wt%; Mg 0.4wt%~1.0wt%; Si 0.4wt%~1.0wt%; The balance is Al and unavoidable impurities; The weight ratio of Si / Mg in the natural anodized aluminum alloy powder is 1:1; The impurity requirements in the natural anodized aluminum alloy powder are as follows: Fe<0.01wt%; Ni<0.01wt%; Mo<0.01wt%; Zn<0.01wt%; Pb<0.01wt%; Sn<0.01wt%; Ti<0.01wt%; Mn<0.01wt%; C<0.01wt%; H<0.01wt%; Na<0.01wt%; Cu<0.01wt%.

5. The method for preparing a natural anodized aluminum alloy powder according to claim 2, characterized in that: The specific operation of the preparation method of the aluminum-magnesium-silicon alloy is as follows: Weighing an aluminum-silicon alloy and placing it in an induction melting furnace, and performing rough melting under the protection of an inert gas to obtain an aluminum-silicon alloy melt, wherein the rough melting temperature ranges from 650° C. to 750° C.; Adding a preset proportion of magnesium silicate powder to the aluminum-silicon alloy melt, and smelting the melt under inert gas protection and mechanical stirring for 1 hour to 4 hours; Rapid cooling and molding to obtain the aluminum-magnesium-silicon alloy; The amount of magnesium silicate used is 2.0wt% to 6.0wt% of the aluminum silicon alloy.

6. The method for preparing a natural anodized aluminum alloy powder according to claim 3, characterized in that: The specific operation of the preparation method of the original powder is as follows: Weigh the required amount of aluminum-magnesium-silicon alloy, pure magnesium, pure aluminum, and aluminum-zirconium alloy, mix them, place them in a suspension smelting device, evacuate to a vacuum degree of ≤3Pa, and fill them with inert gas to standard atmospheric pressure after reaching the standard; The mixed raw materials are suspended and lifted by ultrasonic suspension, and then heated to 650℃~750℃ to melt into molten liquid; Keep the mixture warm and allow to stand for 5 to 30 minutes to prepare the alloy liquid by ultrasonic emulsification. Atomization is achieved by high-speed collision between the inert gas ejected at high speed and the alloy droplets flowing out of the liquid guide tube, and the alloy liquid is broken into small droplets, which are then cooled to obtain the natural color anodized aluminum alloy powder; In the ultrasonic suspension process, the ultrasonic current is set to 15A-30A, and ultrasonic current and power monitoring is set to automatically adjust the ultrasonic current output to prevent ultrasonic attenuation.

7. The method for preparing a natural anodized aluminum alloy powder according to claim 6, characterized in that: The specific operation of the high-speed injection of inert gas is as follows: the inert gas is filled into the atomizing disk below the suspension smelting device, accelerated through the annular cavity, and injected at high speed from the bottom annular gap, with an injection speed of 4-5 Mach, and the annular gap outlet angle of the atomizing disk is 52°.

8. A natural color anodized aluminum alloy powder prepared by the preparation method according to any one of claims 1 to 7.

9. Use of a natural anodized aluminum alloy powder prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The natural anodized aluminum alloy powder is used for consumer electronic products formed by additive manufacturing; The additive manufacturing method is specifically as follows: the natural anodized aluminum alloy powder is subjected to red light fiber laser SLM printing, annealing, wire cutting, surface treatment, heat treatment and then air-cooling to obtain an additive manufacturing product.

10. The use according to claim 9, characterized in that: In the red light fiber laser SLM printing, the laser power is 350W to 450W, the scanning speed is 1000mm / s to 1400mm / s, and the scanning spacing is 0.08mm to 0.12mm; The heat treatment adopts vacuum heat treatment, the insulation temperature is 300℃~500℃, and the insulation time is 4h~6h.

Citation Information

Cited By

  • Method and equipment for determining reference value of additive manufacturing workpiece, medium and product

    CN120927437A

  • Method, device, medium and product for determining a reference value of a part manufactured by additive manufacturing

    CN120927437B